Long‐term cardiovascular mortality after radiotherapy for breast cancer: A systematic review and meta‐analysis. Issue 2 (2nd November 2016) - Sardar, Partha; Kundu, Amartya; Chatterjee, Saurav; Nohria, Anju; Nairooz, Ramez; Bangalore, Sripal; Mukherjee, Debabrata; Aronow, Wilbert S.; Lavie, Carl J
Abstract : Background: Radiotherapy (RT) is frequently associated with late cardiovascular (CV) complications. The mean cardiac dose from irradiation of a left‐sided breast cancer is much higher than that for a right‐sided breast cancer. However, data is limited on the long‐term risks of RT on CV mortality. Hypothesis: RT for breast cancer is associated with long term CV mortality and left sided RT carries a greater mortality than right sided RT. Methods: We searched PubMed, Cochrane Central, Embase, EBSCO, Web of Science, and CINAHL databases from inception through December 2015. Studies reporting CV mortality with RT for left‐ vs right‐sided breast cancers were included. The principal outcome of interest was CV mortality. We calculated summary risk ratio (RR) and 95% confidence intervals (CI) with the random‐effects model. Results: The analysis included 289 109 patients from 13 observational studies. Women who had received RT for left‐sided breast cancer had a higher risk of CV death than those who received RT for a right‐sided breast cancer (RR: 1.12, 95% CI: 1.07‐1.18, P < 0.001; number needed to harm: 353). Difference in CV mortality between left‐ vs right‐sided breast RT was more apparent after 15 years of follow‐up (RR: 1.23, 95% CI: 1.08‐1.41, P < 0.001; number needed to harm: 95). Conclusions: CV mortality from left‐sided RT was significantly higher compared with right‐sided RT for breast cancer and was more apparent after ≥15 years of follow‐up.